O uso do samba de coco como perspectiva de projetos educacionais nas escolas municipais de Arcoverde-PE. - Bezerra, Janayna de Lima (2023)
The theme of this research is: "The use of coconut samba as perspective of educational pro-jects is in the municipal schools of Arcoverde-PE," shows the culture of the samba de c hollow as an educational possibility, working not only its musicality and dance, but, the various edu-cational dimensions that can direct it: History and heritage, religiosity, prejudice and is funny, clothing, letters and languages. Oral history was used as the main methodology, through inter-views, followed by historiographic and iconographic research through images. Personal and illustrative accounts of their traditions, histories and cultural memories not only of the Coquist Masters, but also admirers of this culture. As a result, a product was obtained, specifically a booklet, where it narrates stories and memórias of the Masters of the sambas of Coco Raízes de Arcoverde, Irmãs Lopes and Trupé. From which, the grandeur of the coconut samba culture was demonstrated through reports of experiences and resistances, in the recognition and titra-tion of Arcoverde being traditionally "The land of coconut samba". It envisions the connection with Law.10.369, the DCNERER and the education for relationships is scenic.